Проблеми правового регулювання стартапів в Україні - Лисенко, Ірина В'ячеславівна; Лисенко, Андрій Миколайович; Перевалова, Людмила Вікторівна (Харківський національний університет внутрішніх справ, 2023)
Проведене дослідження присвячено проблемам правового регулювання стартапів у нашій державі. Зокрема, розглянуто теоретико-правову природу стартапів, їхні ознаки, засади функціонування, припинення діяльності, а також залучення інвестиційних капіталів. На підставі проведеного аналізу чинного законодавства та доктринальних доробок запропоновано визначення поняття «стартап», також окреслено ознаки стартапу на підставі дослідження особливостей його правової природи. Запропоновано зробити перелік видів об’єктів інтелектуальної власності відкритим, що сприятиме охороні та захисту інноваційних доробок і напрацювань засновників стартапу.

The article is devoted to the study of the theoretical and legal nature of start-ups, their features, and the legal algorithm of their creation, operation, and termination of activities, with due regard to the existing legislative provisions and doctrinal developments. The rapid technological progress in the world drives the development of economic systems, and the fierce competition between them determines the innovative direction of our country's development. However, despite the fact that over the past two decades new forms of businessUkraine, there have been almost no changes in the legislative field in this area. This state of affairs should make it necessary to amend existing legislative acts and adopt new ones, develop and consolidate new legal terms and concepts, which would facilitate legislative regulation of all innovation processes. To this end, the author proposes to adopt a special Law of Ukraine “On the Activities of Startups” and to enshrine the definition of “startup” therein. The term “start-up” is defined as a business entity registered in accordance with the procedure established by law that offers a competitive innovative service or product, a newly developed or improved technology that will improve a certain area of human activity, but has limited resources. There is also a justified need to make the list of types of intellectual property open. This will help to protect and defend the innovative achievements and developments of startup founders. A list of features inherent in a start-up has been proposed: focus on the development of an innovative product or service; relatively short period of existence with subsequent transformation, sale or termination of existence; scientific potential of the start-up founders; registration of a start-up in the legal form of an individual entrepreneur or a legal entity. The organisational and legal forms of entrepreneurial activity have been analysed and it has been concluded which forms are the most convenient and favourable for registration of start-ups.
Problems of legal regulation of start-ups in Ukraine
Keywords: стартап; інновація; організаційно-правова форма підприємницької діяльності; фізична особа – підприємець; господарські товариства; start-up; innovation; organisational and legal form of entrepreneurial activity; individual entrepreneur; business entities